2010
DOI: 10.1002/adem.201000106
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering, Microstructures, and Mechanical Properties of Macroporous Titanium Foams

Abstract: Porous materials with interconnected porosity have widespread applications in many fields of engineering. [1] Bulk porous metallic materials (honeycomb, foam, and hollow spheres) are known for their interesting combinations of the advantages of a metal (strong, hard, tough, electrically, and thermally conductive, etc.) with the functional properties of porous structures (lightweight with adjustable properties by selecting the density. [2] Because of this, porous metals are interesting for a number of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In this study, the Ti6Al4V foams were fabricated by using PECS at controlled porosity followed by dissolution of NaCl phase and post heat treatment at 1100 o C. Previous investigations showed that high-density pure Ti foams can be fabricated with NaCl as spacer by the PECS at 700 o C for 8 min under 50 MPa [11]. However, the Ti6Al4V/NaCl mixture cannot be densified at the same condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Ti6Al4V foams were fabricated by using PECS at controlled porosity followed by dissolution of NaCl phase and post heat treatment at 1100 o C. Previous investigations showed that high-density pure Ti foams can be fabricated with NaCl as spacer by the PECS at 700 o C for 8 min under 50 MPa [11]. However, the Ti6Al4V/NaCl mixture cannot be densified at the same condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the local surfaces of the particles melt, allowing junctions to be formed between particles in contact. The combination of the PECS technique with a NaCl space holder was used in porous pure Ti to fabricate macroporous Ti foams with controlled architectures recently [11]. This indicated that the PECS may be able to fabricate Ti6Al4V foams from the Ti6Al4V/NaCl powder mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most recently used are partial (loose) sintering of metal powders [28], space holder method [20], spark plasma sintering (porous Ti with yield strength 27.2-94.2 MPa and elastic modulus 6.2-36.1 GPa was derived in [29]), microwave sintering (Ti-6Al-4V/multiwall carbon nanotubes composite with porosity of approximately 25%, yield strength of 145.48 ± 27.28 MPa and elastic modulus of 10.87 ± 2.46 GPa obtained in [30]), combustion synthesis [31], selective laser melting (porous Ti-10Mo alloy with compressive yield strength of 95.59 MPa and an elastic modulus of 4.89 GPa was created in [23]). "3D printing" techniques seems to be most promising among them, since they allow the formation of desired porous structure along with exact implant shape according to the CAD model based on tomography data.…”
Section: Metallic Materials In Orthopedicsmentioning
confidence: 99%
“…The main advantage of the spark plasma sintering technique is very high heating and cooling rates that allow to produce highly dense traditionally difficult-to-sinter materials. A wide range of material types such as nanostructured materials [2], functional-graded materials [3], hard alloys [4], titanium alloys [5], bioceramics [6], porous materials [7] for various applications was fabricated by spark plasma sintering.…”
Section: Introductionmentioning
confidence: 99%